2008
DOI: 10.1007/s00040-008-1007-4
|View full text |Cite
|
Sign up to set email alerts
|

Sperm reduces female longevity and increases melanization of the spermatheca in the bumblebee Bombus terrestris L.

Abstract: Abstract. Here we present evidence that the male mating products (sperm and gland products) reduce survival during hibernation of queens of the bumblebee B. terrestris. Most remarkably, the inseminated queens are significantly more likely to have melanized spermathecae than their virgin sisters. Although we could not detect a direct relationship between these two findings they are quite remarkable since B. terrestris is a monandrous and comparably long-lived insect where sexual conflict is unlikely to evolve. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
0
16
1
Order By: Relevance
“…Although the actual mechanism remains unknown, male genotype also influences queen survival (Korner and Schmid-Hempel 2003). Greeff and Schmid-Hempel (2008) reported that both queens and the males obviously benefit from prolonged survival of the hibernating queen because any sexual conflict is unlikely to occur during this period. Baer and SchmidHempel (2005) found that despite receiving approximately the same total amount of sperm, queens inseminated with a mixture of sperm from two males had a decreased hibernation success compared with queens inseminated with sperm from a single male.…”
Section: Discussionmentioning
confidence: 99%
“…Although the actual mechanism remains unknown, male genotype also influences queen survival (Korner and Schmid-Hempel 2003). Greeff and Schmid-Hempel (2008) reported that both queens and the males obviously benefit from prolonged survival of the hibernating queen because any sexual conflict is unlikely to occur during this period. Baer and SchmidHempel (2005) found that despite receiving approximately the same total amount of sperm, queens inseminated with a mixture of sperm from two males had a decreased hibernation success compared with queens inseminated with sperm from a single male.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Pathogenically, disease transmission may be increased under heightened mating frequency or male presence (see Daly 1978). Accordingly, female fitness could be compromised via this route of sexual conflict (Greeff and Schmid‐Hempel 2008), especially as immune function may be decreased by reproductive activities such as mating (Siva‐Jothy et al 1998). However, again we might expect to see a concurrent increase in female mortality and this was not seen here.…”
Section: Discussionmentioning
confidence: 99%
“…Insemination might thus trigger an increase in proPO transcription, which could then be countered by inhibition of mRNA translation, thus explaining the absence of proPO enzymatic activity. Overall, these results suggest that ant queens, which only mate on a single occasion early in adult life, continue to supress non-self generalist immune recognition in their spermatheca after insemination; this contrasts with the apparent melanization of the bumblebee queen spermathecae after mating (Greeff and Schmid-Hempel, 2008). However, this could possibly be explained by bumblebee queens only using a subset of the sperm stored in their spermatheca to complete their short, oneyear reproductive cycle (Röseler, 1973; Baer and Schmid-Hempel, 2000), so they do not face as strong selective pressure for sperm preservation as long-lived ant queens do.…”
Section: Long-term Sperm Storagementioning
confidence: 86%
“…Melanization in female reproductive organs can be triggered by mating in both non-social and social insects. In Drosophila, copulation sometimes induces the formation of a dark reaction mass in the bursa copulatrix (also called the uterus) (Patterson, 1946) that seems to be related to melanogenesis (Asada and Kitagawa, 1988a,b;Asada and Fukumitsu, 1990), and the spermathecae of bumblebee queens have been observed to become melanized after mating (Greeff and Schmid-Hempel, 2008).…”
Section: Introductionmentioning
confidence: 99%